Effect of the sintering conditions on the electrical properties of Nd(3+) modified PLZT ceramics - Roca, R. Alvarez; Botero, E. R.; Guerrero, F.; Guerra, J. D. S. [UNESP]; Garcia, D.; Eiras, J. A. (Iop Publishing Ltd, 2008)
The effect of the sintering method on the microstructural and electrical properties of (Pb(0.89)Nd(0.02)La(0.09))(Zr(0.65)Ti(0.35))O(3) (PNLZT) ceramics was studied by impedance spectroscopy. Structural and microstructural analyses were performed using x-ray and scanning electron microscopy techniques. Two different sintering routes were employed: the conventional and the hot-pressing sintering methods. The impedance analysis provided a convincing evidence for the existence of both grain (g) and grain boundary (gb) contributions to the conduction process. An equivalent circuit for the impedance behaviour has been proposed and discussed. The variation in the sintering method produces significant changes in the grain and grain boundary conductivities. For the grain effect, the main conduction mechanism has been associated with oxygen vacancy migration. Otherwise, for grain boundary conductivity the impedance behaviour has been discussed in terms of the brick-layer and the constriction resistance models (BLM and CRM, respectively).